Pengaruh persepsi harga, persepsi kualitas, dan persepsi merk terhadap minat pembelian mobil merk Wuling di Kota Jambi - Maruli Asi Tua Sihombing; Johannes Johannes; Novita Ekasari (Jurnal Dinamika Manajemen, 2021)
This study aims to analyze the effect of price perception, perceived quality, and brand perception on the purchase interest of Wuling cars in Jambi City, and to find out which variables are more dominant in influencing Wuling car purchase interest in Jambi City. This thesis uses a quantitative descriptive approach, namely research by emphasizing its analysis on numerical data (numbers) processed by statistical methods, namely quantitative data collected through measurement, namely multiple regression analysis. The results showed that 1. Price perception, quality perception, and brand perception together have a significant and positive effect on purchase intention. Partially price perception and perception of quality have a significant and positive effect on purchase intention, while brand perception does not have a significant and positive influence on purchase intention. 2. Perception of dominant quality has a significant and positive effect on purchase intention.